Extremspänningsautomatikens inverkan på spänningsstabilitet - Larsson,Martin (CODEN:LUTEDX/TEIE-5, 2012)
This master thesis is a pilot study on what impact different strategies for automatic switching of reactive shunts have on voltage stability in an electric power system. A dynamic analysis has been performed through real-time simulations in ARISTO on the NORDIC32-svedala system. Seven different switching strategies are examined in two different but common scenarios for the Nordic power system. The principles behind the automatics are described and examples of implementation are supplied through parameter settings and net diagrams. It is shown that the time settings of individual automatics have an impact on overall system performance and that quick action is crucial in situations where voltage collapse is imminent. By decreasing time delays for automatics system wide better performance can be achieved. It is also shown that, by letting the automatics take adjacent voltages into account, in this scenario the collapse can be avoided.
Keywords: Spänningsstabilitet; shunt; reaktiv effekt; elkraftsystem; Svk; Svenska Kraftnät; Extremspänningsautomatik; voltage collapse; voltage stability; NORDIC32; reactive power; voltage automatics; spänningskollaps; ARISTO